Origin of Electron‐Scale Magnetic Fluctuations Close to an Electron Diffusion Region. Issue 5 (10th May 2021) - Hoilijoki, S.; Pucci, F.; Ergun, R. E.; Schwartz, S. J.; Wilder, F. D.; Eriksson, S.; Chasapis, A.; Ahmadi, N.; Webster, J. M.; Burch, J. L.; Torbert, R. B.; Strangeway, R. J.; et al.
Abstract: During a dayside magnetopause crossing, the Magnetospheric Multiscale (MMS) mission observed a series of magnetic depletions in the total magnetic field, mainly due to the fluctuation of the component normal to the magnetopause. These fluctuations are adjacent to signatures suggesting that the MMS is at, or close to (< d i ), a magnetic reconnection electron diffusion region (EDR). The temporal and spatial scales of the fluctuations are too short for the ions to be affected. In this paper we investigate the origin of these fluctuations, finding that they can develop from temporal variations of the reconnection rate at the nearby EDR. Indeed asymmetric reconnecting current sheets, and the nearby regions, are subject to multiple different instabilities, and may be affected by waves and turbulence activity. Here we suggest such oscillations in the normal component of the magnetic field can be interpreted either as i) electron‐scale structures, forming due to changes in the outflow speed and the corresponding changes in the angle between the separatrices, causing magnetic field to pile up or ii) electron vortices generated by enhanced sheared electron outflows, driving electron‐scale Kelvin–Helmholtz instability. Key Points: A series of five large amplitude electron‐scale magnetic fluctuations is observed at the dayside magnetopause The largest fluctuating magnetic field component is the component normal to the magnetopause These fluctuations could be caused by temporal variations of the reconnection rate or induced by electron vorticity